Clinical and electrophysiological features of Guillain-Barré syndrome: A 7-year experience of Hacettepe University Department of Neurology - Çakar, Merve Melodi; Demirel, Mert; Yıldız, Fatma Gökçem; Erdem Özdamar, Sevim; Bekircan-Kurt, Can Ebru; Temuçin, Çağrı Mesut (Acta Medica, 2025)
Objective: Guillain-Barré Syndrome (GBS) is the most common cause of severe acute paralytic neuropathy. In this retrospective study, we present the GBS experience of the Hacettepe University Department of Neurology and discuss the clinical and electrophysiological features. Material and Methods: Demographic data, presenting complaints, cerebrospinal fluid (CSF) findings, EMG results, and treatments of patients with electrophysiological findings compatible with GBS between August 2017 and August 2024 were retrospectively reviewed. Results: Fifty-nine patients diagnosed with GBS (41 males, mean [min-max] age 49 [3–92] years) were recorded. Among them, 66% (n=39) were classified as AIDP, 22% (n=13) as AMAN, 3% (n=2) as AMSAN, and 9% (n=5) as MFS. It was noted that EMG was performed within an average of 11 days after the onset of the first symptom. Sensory complaints were the initial symptoms in half of the patients. Six patients (10%) required mechanical ventilation during follow-up. Prolonged or absent F-waves in one or more nerves were recorded in 64% (n=38) of upper limbs and %90 (n=53) of lower limbs. Reduced distal compound muscle action potentials (CMAP) in two or more nerves were observed in 51 patients (86%), prolonged distal motor latency (DML) in two or more nerves in 40 patients (68%) and slowed motor nerve conduction velocities (NCV) in two or more nerves in 26 patients (44%). Sural SNAP amplitudes were normal in 33 patients (56%), decreased in 14 (24%), and absent in 12 (20%). The conduction block was recorded in 10 patients (17%), and temporal dispersion was noted in 19 patients (32%). Treatment included IVIg in 40 patients (68%) and plasmapheresis in 2 (3%), and due to insufficient treatment response, the number of patients requiring plasmapheresis after IVIg or vice versa was 13 (22%). Conclusion: This study showed that AIDP is the most common electrophysiological subtype of GBS in our population. Our study found that AIDP was GBS’s most common electrophysiological subtype. Prolonged or absent F-waves reduced distal CMAP amplitudes, prolonged DML, slowed NCV, decreased upper limb SNAP amplitudes, and partially preserved sural sensory responses observed in our study were consistent with the findings of other studies.